Mortality and hospital admissions from poisonings and adverse drug reactions in Espírito Santo: a time series analysis (Revista Brasileira Multidisciplinar, 2026)
Drug poisonings and adverse drug reactions have become significant factors causing hospitalizations and deaths, making it a topic of great importance in public health. This study investigates the number of deaths and hospital admissions due to drug poisonings and adverse drug reactions in the state of Espírito Santo. Data from the Mortality Information System (SIM) and the Hospital Information System (SIH) of the Brazilian Unified Health System (SUS) were used for the period from 2010 to 2020. The events were classified according to the codes of the 10th International Statistical Classification of Diseases and Related Health Problems (ICD-10), and the trend of the historical series was evaluated through generalized linear regression using the Prais-Winsten method. In total, there were 264 deaths and 10,622 hospitalizations related to drugs, with the most prevalent record of poisoning occurring in brown-skinned individuals under 60 years old. The average age was lower in cases of poisoning compared to adverse reactions in both outcomes. The leading cause of death was intentional self-poisoning due to exposure to anticonvulsant drugs, hypnotics, antiparkinsonian agents, and unspecified psychotropic drugs. In the case of hospitalizations, mental and behavioral disorders due to the use of multiple drugs and other psychoactive substances, including psychotic disorders, predominated. Drug poisonings and adverse drug reactions play a relevant role in the occurrence of deaths and hospitalizations in the state of Espírito Santo. These findings are important since many cases of poisonings and adverse reactions can be considered preventable.
Keywords: Medications; Adverse Drug Reactions; Medication Mortality; Health Information Systems